Strategi dalam Memerangi Korupsi: Analisis Multi-Dimensi terhadap Kebijakan Anti-Korupsi dan Dampaknya: (Studi Kasus Kepala Desa Banjar Sari Lombok) - Nadia Adinda Kezia Panjaitan (Supremasi Hukum: Jurnal Penelitian Hukum, 2024)
Corruption is a significant issue plaguing society, with detrimental consequences for national development. It involves the abuse of authority and public trust for personal gain or the interests of specific groups, adversely affecting the government, private sector, non-governmental sectors, and society at large. This research aims to conduct a multi-dimensional analysis of anti-corruption policies implemented in the Head of Village Banjar Sari Lombok region and their resulting impacts. The study encompasses various strategies, including legal aspects, combating corruption in the public sector, preventive measures, anti-corruption education, and community involvement. Additionally, the research investigates how anti-corruption policies have affected various aspects of social, economic, and political life in the Head of Village Banjar Sari Lombok. The research methodology includes a literature review, framework development, data collection, analysis, case studies, impact assessment, recommendations, and validation. This methodology provides comprehensive insights into the efforts against corruption and the effectiveness of anti-corruption policies in the Head of Village Banjar Sari Lombok. Research findings demonstrate that anti-corruption policies have resulted in positive changes in governance, enhancing transparency, accountability, and public awareness of corruption risks. These impacts also extend to the economic realm, reducing economic losses due to corrupt practices. Therefore, efforts to combat corruption in the Head of Village Banjar Sari Lombok must be continually strengthened and improved to ensure a cleaner society and a more advanced community.